Analisis Paralelisme dalam Puisi Hilang (Ketemu) Karya Sutardji Calzoum Bachri - Wijaya, Satria; Destiani, Destiani; Putri, Tiara Herya (Universitas Lampung, 2023)
Poetry ‘Hilang (Ketemu)’ a signature work by Sutardji Calzoum Bachri, is presented in a beautiful stanza with the selection of diction as its characteristic. The forms of meaning and typography displayed in his poetry also embellish the style of language in his poems. This study aims to analyze the use of figurative language namely parallelism, assonance, alliteration, and the meaning contained in the poetry ‘Hilang (Ketemu)’. This research is a type of qualitative research. The data in this study is in the form of an array of poetry by Sutardji Calzoum, ‘Hilang (Ketemu)’ which contains figurative language. Data collection techniques used in the form of see, read, note. Furthermore, the data analysis technique used is descriptive qualitative. The data analysis steps used were reading and listening to the poetry ‘Hilang (Ketemu)’; then analyze the style of language used in it; grouping the results of data analysis; describe the results of the analysis. The results of this study indicate that the poetry ‘Hilang (Ketemu)’ contains figurative language in the form of parallelism, assonance, alliteration, repetition, and meaning.Puisi yang berjudul ‘Hilang (Ketemu)’ ciptaan Sutardji Calzoum Bachri disuguhkan dalam bentuk bait yang indah dengan pemilihan diksi sebagai ciri khasnya. Bentuk makna maupun tipografi yang ditampilkan dalam puisinya turut memperindah gaya bahasa dalam puisi-puisi karyanya. Penelitian ini bertujuan untuk menganalisis penggunaan gaya bahasa yakni paralelisme, asonansi, aliterasi, dan makna yang terkandung di dalam puisi ‘Hilang (Ketemu)’. Kajian ini ialah salah satu kajian kualitatif. Data dalam kajian ini berupa larik puisi ‘Hilang (Ketemu)’ karya Sutardji Calzoum yang mengandung gaya bahasa. Teknik untuk menggumpulkan data ialah simak, baca, catat. Selanjutnya teknik untuk menganalisis data berupa deskriptif kualitatif. Langkah-langkah kajian dalam menganalisis data, yakni membaca dan menyimak puisi ‘Hilang (Ketemu)’; selanjutnya menganalisis gaya bahasa yang digunakan di dalamnya; mengelompokkan hasil analisis data; mendeskripsikan hasil analisis. Hasil dari penelitian ini menunjukkan puisi ‘Hilang (Ketemu)’ mengandung gaya bahasa berupa paralelisme, asonansi, aliterasi, repetisi, dan makna. Keywords: Alliteration, Assonance, Parallelism, Poetry, Repetition.